Emerging treatment evolutions and integrated molecular characteristics of biliary tract cancers. Issue 12 (6th October 2021) - Zhang, Ruyi; Puzzoni, Marco; Mariani, Stefano; Zheng, Yi; Liscia, Nicole; Guo, Yixuan; Donisi, Clelia; Liu, Yu; Impera, Valentino; Fang, Weijia; Scartozzi, Mario
Abstract: Biliary tract cancers (BTCs) consist of a group of highly heterogeneous malignancies that are characterized by genomic differences among tumors from different anatomic sites. The current treatment for BTC includes surgery, chemotherapy, target therapy, and immunotherapy. Although surgery remains the primary option for localized disease, representing the only potential curative treatment, a high risk of recurrence cannot be neglected. Chemotherapy has been considered the standard of care for both advanced and metastatic disease and in adjuvant settings. However, drug resistance is a major obstacle associated with chemotherapy. The development of genetic testing technologies, including next‐generation sequencing, has opened the door for the identification of drug targets and candidate molecules. A series of preclinical studies has demonstrated the role of gene mutations, abnormal signaling pathways, and immunosuppression in the pathogenesis of BTC, laying the foundation for the application of targeted therapy and immunotherapy. A variety of molecularly targeted agents, including pemigatinib, have shown promising survival benefits in patients with advanced disease. The rapidly evolving role of multimodal therapy represents the subject of this review. Abstract : Biliary tract cancers (BTCs) consist of a group of highly heterogeneous malignancies, which are characterized by genomic differences among tumors from different anatomic sites. A series of preclinical studies have proven the role of gene mutations, abnormal signaling pathways, and immunosuppression in the pathogenesis of BTC, laying the foundation for the application of targeted therapy and immunotherapy. The disappointing response to conventional cytotoxic drugs along with the genetic heterogeneity of BTC led to both immunotherapy and targeted therapy–oriented research based on the genetic characterization of BTC.